2023
DOI: 10.1039/d3sc02078a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic-dependent selectivity in a bisphosphine iron spin crossover C–H insertion/π-coordination reaction

Michael T. Davenport,
Justin K. Kirkland,
Daniel H. Ess

Abstract: Organometallic reaction selectivity is governed by dynamic motion rather than transition states or spin crossover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…They found that π-complexation of the alkene is thermodynamically favored with respect to the oxidative addition of vinylic sp 2 C–H bonds. Moreover, the π-complex was found to be not an intermediate in the lowest energy C–H activation process. , Computational studies support the conclusions and suggest that π-coordination and C–H activation of the alkene are separate and competitive pathways. …”
Section: Introductionmentioning
confidence: 99%
“…They found that π-complexation of the alkene is thermodynamically favored with respect to the oxidative addition of vinylic sp 2 C–H bonds. Moreover, the π-complex was found to be not an intermediate in the lowest energy C–H activation process. , Computational studies support the conclusions and suggest that π-coordination and C–H activation of the alkene are separate and competitive pathways. …”
Section: Introductionmentioning
confidence: 99%